Implementing the Emotional Openness Model through Inclusive Staging: A Therapeutic Approach for Children with Disabilities - Precillia, Monita (Jurnal Psikiatri Surabaya, 2025)
Introduction: This study explores the utilization of the emotional openness model through the inclusion stage as an innovative therapeutic approach to enhance emotional expression in children with disabilities. This therapeutic approach is designed to provide a platform for emotional expression and social interaction through the performance “I Love the Sea.” Methods: include participatory observation, interviews, and analysis to assess the impact of the stage therapy program on the emotional openness of the children. Results: indicate significant improvements in positive emotional expression, enhanced interpersonal communication skills, and increased self-confidence among the participants. The study demonstrates that the inclusion stage approach serves as a therapeutic medium, creating a space for children with disabilities to express themselves creatively and foster more open social relationships. Conclusion: the implementation of the emotional openness model through the inclusion stage offers an innovative and inclusive solution to strengthen the emotional aspects of children with disabilities, supporting active interaction and enhancing their social integration.